Models of English Learning for Students with Disabilities at SLB Negeri 1 Sidrap - Wiwi Anjelina; Syamsu Tang; Sitti Aisa; Nur Hikmah; Sam Hermansyah (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
This study investigates the models of English learning implemented for students with disabilities at SLB Negeri 1 Sidrap and evaluates how these models influence students' motivation to learn English. Employing a qualitative research design, data were gathered through observations, interviews, and document analysis. The results reveal that students show a strong preference for video-based and interactive learning activities. Teachers adopt diverse instructional strategies, including multisensory learning, game-based learning, and collaborative approaches, all tailored to meet students' individual needs. Despite these efforts, challenges persist, particularly in mastering tenses and maintaining focus during lessons. To overcome these obstacles, teachers offer personalized support, re-explain complex concepts, and assist slow writers by dictating materials. The findings highlight the crucial role of adaptive teaching strategies in enhancing the English learning experience for students with disabilities in special education settings.